Epigenetic landscape reveals MEF2 and SIX family-mediated transcriptional networks underlying dietary NFC/NDF ratio-induced muscle development and meat quality in Tibetan sheep - Sa, Rengeerli; Zhang, Fengshuo; Yang, Zhenglu; Shi, Chengdi; Hou, Shengzhen; Zhang, Song; Gui, Linsheng (Frontiers in Nutrition, 2025)
IntroductionWe investigated epigenetic mechanisms underlying muscle development in black Tibetan sheep fed different dietary ratios of non-fiber carbohydrate to neutral detergent fiber (NFC/NDF), integrating phenotypic analyses (growth performance, meat quality, muscle histomorphology) with multi-omics approaches (ATAC-seq, H3K27ac CUT&Tag, RNA-seq).MethodsThe subjects were 2-month-old weaned male Tibetan sheep with an initial body weight of 10.45 ± 0.96 kg. Using a completely randomized study design, 90 sheep were randomly assigned to three treatment groups with 30 sheep per group. Each treatment group consisted of 5 pens with 6 sheep per pen. The dietary NFC/NDF ratios of these three treatment groups were 0.71 (Group L), 1.16 (Group M) and 1.82 (Group H).ResultsAn NFC/NDF ratio of 1.82 yielded optimal growth performance with increased live weight, carcass weight, and dressing percentage. This ratio significantly improved meat tenderness, water-holding capacity, and pH values while reducing hardness and chewiness, accompanied by compact muscle fiber architecture. Epigenomic analyses revealed epigenetic signals predominantly localized within distal intergenic regions (10–100 kb). Enhancers showed dynamic responsiveness to dietary NFC/NDF changes, with MEF2 and SIX transcription factor binding sites enriched in upregulated enhancers. RNA-seq confirmed functional associations between epigenetic modifications and gene expression, revealing enrichment of fatty acid metabolism, epithelial cell proliferation, and macrophage chemotaxis pathways. Differential expression of key genes (EGR3, FGF7, HPGD, C5, EDNRB) corroborated MEF2 and SIX families’ central role in nutrient-mediated muscle remodeling.DiscussionThese findings elucidate how dietary NFC/NDF ratios optimize muscle development through enhancer activation, providing insights for precision nutrition strategies in livestock production.